(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Physical training in karate has historically relied on traditional means (kihon , kata, kumite, general physical training), but in recent years modern methods of conditioning training (strength training, plyometrics, HIIT/ sprint intervals, core) have been increasingly introduced. Training, combined protocols). The purpose of this article is to briefly summarize research data on the effectiveness of traditional and modern approaches in karate and outline practical implications for training (especially for kumite). The literature has consistently shown that modern methods, especially plyometrics, strength, and interval protocols, produce significant improvements in power, jumping, speed-coordination, and certain specific qualities (change of direction, striking technique), provided they are adequately dosed and combined with specialized techniques.